Cover - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
Handling Selection of Compression And Stability Problems of Embankment Based on The Thickness of Soft Soil Layer Below (Case Study: Rengat – Pekanbaru Toll Road Project Sta. 176+775 – Sta. 176+975) Pandu Hermawan, Noor Endah Mochtar, Indrasurya B. Mochtar, & Mahar Muliawan Slope Stability Analysis Under Dry-Wetting Cycle Conditions (Case Study: Landslide Countermeasure of Batas Pidie/Aceh Besar - Batas Kota Sigli) Zulfadhli, Trihanyndio Rendy Satrya, Ria Asih Aryani Soemitro & Fikri Afzal Alternative Planning Slope Stabilization On Roadway Case Study : Landslide On Tabone-Polewali Road Section KM 168+790 to 168+820 Ismi Istiqamah, Mohamad Khoiri, Mahendra Andiek Maulana & Bambang S. Razak Study of The Behavior of Abutment Piled Foundation due to Nearby Staged-Embankment (Case Study: Kali Kandang Bridge on The North Ring Road of Lamongan) Azkiya Nabila, Trihanyndyo Rendy Satrya, Ria Asih Aryani Soemitro, Sifa Udukha Behaviour Study of Abutment Pile Foundation on Lightweight Embankment Oprit(Case Study: Kali Otek Bridge – Lamongan North Ring Road Construction Package Section 2) Nila Wahyu Pertiwi, Ria Asih Aryani Soemitro, Trihanyndio Rendy Satrya, Sifa' Udukha